СПИСКИ (ПЕРЕЛІКИ, РЕЄСТРИ) НЕМАТЕРІАЛЬНОЇ КУЛЬТУРНОЇ СПАДЩИНИ - Кудерська, Надія Іванівна, Кудерська Ірина Олександрівна (SUPREMANCE OF LAW, 2016)
Studied the legal basis for creating and maintaining lists (lists, registers) intangible cultural heritage; characterized national lists (lists, registers) intangible cultural heritage; The basic criteria for intangible cultural heritage for inclusion in the Representative List of the Intangible Cultural Heritage UNESCO List of Intangible Cultural Heritage in need of urgent protection of UNESCO, national lists (registers) intangible cultural heritage.
Keywords: Intangible cultural heritage lists (registers); criteria.